2013
DOI: 10.1155/2013/593517
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Cardiovascular Regenerative Medicine: Directing Tissue Repair and Cellular Differentiation

Abstract: MicroRNAs (miRNAs) are a class of short noncoding RNA molecules, approximately 22 nucleotides in length, which regulate gene expression through inhibition of the translation of target genes. It is now generally accepted that miRNAs guide processes and cellular functions through precise titration of gene dosage, not only for a single gene but also controlling the levels of a large cohort of gene products. miRNA expression is altered in cardiovascular disease and may thereby limit and impair cardiovascular repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 137 publications
(157 reference statements)
0
12
0
Order By: Relevance
“…Likewise, MSC secretome with mobilizing factors HGF, LIF, SDF-1, SCF and VE-Cadherin was purported to increase mobilization and homing of endogenous MSCs in adult DCM hamsters [143]. Numerous microRNAs have been identified to modulate cardiac repair and regeneration [144,145] and these microparticles have also been identified as immature mRNA when secreted from MSCs [146]. Additional contents of MSC exosomes include CD81, CD9 and Alix, which reduced infarct after injection in an ischemia/reperfusion injury mouse model [147].…”
Section: Current Status Of Adult Stem Cell Therapiesmentioning
confidence: 99%
“…Likewise, MSC secretome with mobilizing factors HGF, LIF, SDF-1, SCF and VE-Cadherin was purported to increase mobilization and homing of endogenous MSCs in adult DCM hamsters [143]. Numerous microRNAs have been identified to modulate cardiac repair and regeneration [144,145] and these microparticles have also been identified as immature mRNA when secreted from MSCs [146]. Additional contents of MSC exosomes include CD81, CD9 and Alix, which reduced infarct after injection in an ischemia/reperfusion injury mouse model [147].…”
Section: Current Status Of Adult Stem Cell Therapiesmentioning
confidence: 99%
“…Once considered transcriptional noise, several transcriptome studies have shown prevalent transcription of a large number of non-coding RNAs (ncRNAs) (2). These ncRNAs are classified into two groups according to their length, whereby small ncRNAs are arbitrarily set at less than 200 nucleotides in size and include several ncRNAs species including small interfering RNAs (siRNAs), Piwi-interacting RNAs (piRNAs) and microRNAs (miRNAs) (3)(4)(5). In addition, transcripts of ncRNAs that are larger than 200 nucleotides are called long non-coding RNAs (lncRNAs).…”
mentioning
confidence: 99%
“…Several growth factors which regulate these interactions have been identified and described. 66 Recently, miRNAs were identified as tight regulators 67 and EC were shown to secrete miR-126 and target SMCs, thereby regulating their turnover in vitro and in vivo in a paracrine manner. Although mediation via vesicles was studied, the authors observed that a non-vesicle fraction was responsible and that Argonaute-2-bound miR-126 was transferred to the SMCs, subsequently blocking forkhead box O3, B-cell lymphoma 2, and insulin substrate 1 mRNAs, while stimulating neointimal lesion formation.…”
Section: Vesicles In Endothelial Communicationmentioning
confidence: 99%